Media Sosial dan Iklan: Pengaruh Brand Awareness Terhadap Minat Beli Produk Skincare Glad2Glow - Saputra, Muhammad Rizal; Khoirunnisa', Lina Febriana (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
This study analyzes the influence of social media and digital advertising on consumers' purchase intention for Glad2Glow, with brand awareness as a mediating variable. Based on a survey, 60% of Indonesia’s population actively uses social media for an average of three hours daily, making it a crucial channel for marketing. The study involved 190 respondents selected using simple random sampling, with data collected through an online questionnaire. Analysis using Smart PLS revealed that social media and digital advertising have a positive and significant impact on brand awareness and purchase intention. Brand awareness also mediates the influence of these variables on purchase intention. The R Square value shows that 78.6% of purchase intention variability is explained by social media, digital advertising, and brand awareness. These findings highlight the importance of effective digital marketing strategies to enhance brand awareness and boost consumer purchase intention